Minimally invasive tubular versus conventional open microsurgery of the lumbar spine for degenerative disorders - Michal Ziga; Ahmed El-Garci; Julia Mahler; Evangelos Kogias; Rainer Schlichtherle; Oliver Bozinov; Martin N. Stienen; Yashar Naseri (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background The aim of this study was to investigate patient-related variables, hospital-related variables and surgeon-related variables of minimally invasive tubular microsurgery (MITM) compared to conventional open microsurgery (COMS) in patients undergoing microsurgery for lumbar degenerative disorders (LDD). Results 403 included patients were treated microsurgically for LDD between 09/2018 and 09/2021. Mean blood loss (44 vs. 72 ml), surgery time (76.2 vs. 85.7 min) and mean Rx-Dosis (1.1 mGy vs. 1.6 mGy) were lower in the MITM group (all p < 0.05). The Macnab criteria and VAS pain scale (VAS Leg/VAS Back) of the MITM group were better at 6 weeks as well as 1 year postoperatively (Macnab at 6W: 1.5 vs. 1.7 (p = 0.02), at 1y: 1.2 vs. 1.4 (p = 0.002); VAS Leg at 6W: 1.4 vs. 1.9 (p = 0.005), at 1y: 0.4 vs. 0.9 (p < 0.001), VAS Back at 6W 1.4 vs. 3.2 (p < 0.001), at 1y: 1.2 vs. 1.4 (p < 0.001)). Conclusion The patient-related variables, hospital-related variables and surgeon-related variables are equivalent or better in MITM compared to COMS. MITM showed more favourable clinical outcomes in both short- and long-term follow-up, albeit small between-group differences in our single-center study and can be considered for various microsurgical indications for LDD.